England in the Poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2018)
This research is a comparative literature study. It is a series of studies about Ahmad Shawqi, Prince of Arab poets. Shawqi’s relationship with the English and its impact on his poetry was investigated, exploring his youth, partly spent in Europe, and some aspects of his autobiography. Shawqi wrote poetry recognizing many English occasions, such as the coronation of Edward VII, and remembering the English writer Hall Cane, author of the White Prophet. The poem in which Shawqi addressed Lord Cromer and which caused him to be exiled to Spain, was examined, as was his journey to Spain and his poems about the English, such as his lament of Kitchener. Shawqi’s return to Egypt and the rise of the 1919 revolution against the English occupiers was also probed, revealing how this poet of the palace became a poet of the people. Conclusively, the English poet William Shakespeare is shown to have had an influence on Shawqi’s plays and poetry. This research is accompanied by several translated poems addressing these topics.